STUDI OF STABILITY AND SETTLEMENT OF PILE GRUP SYSTEM OF LARGE JETTY IN WEST KALIMANTAN - Annafis Milda, Asyifah
The Port of West Kalimantan is currently under construction, will later become one of the largest ports in Indonesia. The jetty was designed to be able to serve ships up to 100,000 DWT. Such a large ship is required deep draft to berth that the jetty has to be located away from the beach. Therefore the pile foundation has an approximate free standing of 22m. The Jetty with a platform of 100,000x100 m is connected by a trestle of 35km. The soil profile at the jetty is dominated by soft to medium stiff clays up to 57 meters below the ground surface and hard clays were not found to the depth of 80 meters below the ground surface, so that the friction pile is designed with varying lengths from 64m to 84m. Main challenge of this final project is consolidation settlement. Since the soft clays is highly compressible so the soil will potentially be compressed significantly. The calculation of settlement in this final project utilized FEM (Finite Element Method) and 1-D Consolidation by Terzaghi. Both methods were selected to estimate settlement at each pile. In addition to stability,the settlement also became the consideration in determining the length of the pile. The length of the pile was designed to comply stability, settlement and differential settlement criteria. Treatment of pile head is also important, so that the forces in the superstructure can be properly transmitted to the pile foundation. The pile head is designed to resist moment and pullout forces. The results of analysis in this large jetty is required length of pile varying about 64 meters up to 84 meters with total settlement about 4cm to 10cm.